IMPLEMENTASI PENDIDIKAN MORAL DAN NILAI KEISLAMAN MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM MAN 2 PONTIANAK - Rahmawaty Rahmawaty; Agus Sastrawan Noor; Ika Rahmatika Chalimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract This research aims to find out about the implementation of moral education and islamic vaalues in the subjectsof islamic cultural history in class XII social sciences MAN 2 Pontianak. The research method used descriptive research form. Data sources of this research was history teacher of islamic culture and students class XII social sciences. Data collection techniques, while the data collection tools used were observation guides, interview guides, and documentation. The analysis in this study was presented in a descriptive qualitative manner using 16 informants. The result of this study indicates that planning in the implementation of moral education and islamic values with the implementation plan of learning. Implementation of moral education and islamic values encompasses reading the Quran before starting the lesson, peeling historical material, evaluating and closing with prayer. Evaluation of the implementation of moral education and islamic values by checking directly with students relate to the order of the agreed rules, if it violates the rules then it is subject to sanctions. Constraints and solutions for the implementation of moral education and islamic values, were specifically the lack of control by the teacher of students, so there are still students who break the rules. The solution is to do better supervision and always give advice, reprimand students who make mistakes. Keywords: History Of Islam, Implementation, Islamic Values, Moral